The use of dimethylsulfoxide as a solvent in enzyme inhibition studies: the case of aldose reductase. (1st January 2017) - Misuri, Livia; Cappiello, Mario; Balestri, Francesco; Moschini, Roberta; Barracco, Vito; Mura, Umberto; Del-Corso, Antonella
Abstract: Aldose reductase (AR) is an enzyme devoted to cell detoxification and at the same time is strongly involved in the aetiology of secondary diabetic complications and the amplification of inflammatory phenomena. AR is subjected to intense inhibition studies and dimethyl sulfoxide (DMSO) is often present in the assay mixture to keep the inhibitors in solution. DMSO was revealed to act as a weak but well detectable AR differential inhibitor, acting as a competitive inhibitor of the L-idose reduction, as a mixed type of non-competitive inhibitor of HNE reduction and being inactive towards 3-glutathionyl-4-hydroxynonanal transformation. A kinetic model of DMSO action with respect to differently acting inhibitors was analysed. Three AR inhibitors, namely the flavonoids neohesperidin dihydrochalcone, rutin and phloretin, were used to evaluate the effects of DMSO on the inhibition studies on the reduction of L-idose and HNE.